How Duty-Free Policy Influences Travel Intention: Mediating Role of Perceived Value and Moderating Roles of COVID-19 Severity and Counterfactual Thinking - Xu, Yajun; Ma, Wenbin; Xu, Xiaobing; Xie, Yibo (Frontiers in Psychology, 2022)
Counterfactual thinking is presumed to play a preparatory function in promoting people’s behavioural intentions. This study specifically addresses the impacts of COVID-19 severity, tourists’ counterfactual thinking about the pandemic, and tourists’ perceived duty-free consumption value on the effect of a duty-free policy on travel intentions. Four hundred and ten participants took part in this study, which involved a 2 (duty-free policy: absent vs. present) × 2 (COVID-19 severity: high vs. low) design. Results reveal the following patterns: (a) compared to the absence of a duty-free policy in tourist destinations, enactment of a duty-free policy leads to stronger visit intentions through greater perceived value; and (b) the effect of a duty-free policy on travel intention is moderated by tourists’ counterfactual thinking and COVID-19 severity.